Institutions Private Higher Education: The Prouni and Quality of Education - Valeria Jabur Maluf Mavuchian Lourenço; Vladmir Oliveira da Silveira (Revista de Direito Sociais e Políticas Públicas, 2016)
Private higher education institutions have business activity and the public mission of fulfilling the constitutional principle of the fundamental right to education. In this sense, the federal government instituted the PROUNI, in order to promote social inclusion of low- income people by providing scholarships, providing access to higher education in these institutions. This study, using hypothetical deductive method, bibliography and data, seeks to respond not only with regard to access to higher education by the program and the distribution of grants, as well as the quality of teaching in the exercise of the social function by higher education institutions, as companies.